ISTISHAB: SEJARAH DAN POSISINYA - Misbahuzzulam, Misbahuzzulam (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2013)
Determine specific legal for a problem must be based on the arguments or reasons that support it. In determining the law, al-Quran and al-Sunnah is often used by the scholars. But in turn, the second source of law is sometimes deemed not sufficient to determine the law on any issue, it is caused due to a variety of new problems are always popping up along with the times. The scholars are trying to find solutions to any problems that arise. Then counterposed the variety of methods that necessarily all of them can not be separated from the corridor shari'ah, such as Ijma', Qiyas, Istihsan, 'urf, Maslahah mursalah, Shar 'Man Qablana, qawl Sahabiy, Istishab and so on. In this short paper, the author will discuss about Istishab as one method of determining the law. Starting from Istishab meaning, pillars, conditions, their types, the rules that appear in it as well as its position in determining the particular law.